Acid-activated Carbons from Peanut Shells: Synthesis, Characterization and Uptake of Organic Compounds from Aqueous Solutions - Romero, Luis Cesar (2003)
Activated carbon with a high adsorption capacity for the removal of organic compounds from aqueous solutions was made from phosphoric acid-activated peanut shells. Adsorption isotherms for the uptake of phenol, iodine, Methylene Blue and tannic acid were obtained at 22°C. Freundlich, Langmuir and previously developed equation models all explained the experimental data satisfactorily. Further analysis using the Dubinin-Radushkevich equation showed that the maximum micropore volume accessible to the adsorbate decreased as the molecular size increased, suggesting a molecular sieve or gate effect. A comparison was made with the micropore volume as determined by nitrogen adsorption at -196°C. The results presented indicate that peanut shell residues provide a suitable option for the preparation of activated carbon with good surface properties and the ability to remove organic compounds from aqueous solutions.